Optimizing Solar Panel Output with an IoT-Based Solar Tracker: UNIPMA Integrated Lab Case Study - Irna Tri Yuniahastuti; Ina Sunaryantiningsih; Arizhal Firmansyah; Dian Faisal Akbar (Universitas Negeri Padang, 2024)
The development and development of new renewable energy has become increasingly widespread recently, one of the most widely used is solar panels. The biggest disadvantage of installing solar panels is that they are not able to follow the movement of the sun so that the power output produced is less than optimal. A solar tracker is a device used to optimize the absorption of sunlight by solar panels by following the movement of the sun. However, the use of sensors on solar trackers often requires quite complicated manufacturing. Therefore, this research aims to design a solar tracker without sensors in photovoltaic (PV) systems. The method in this research is to compare the power produced by solar panels with and without solar trackers based on IoT (Internet of Things) case studies at the UNIPMA Integrated Lab. Data collection was carried out in real time over a period of 3 days starting at 09.00 WIB with a solar panel tilt of 45° until 15.00 WIB with a solar panel tilt of 135°. The results of measurements using a solar tracker on photovoltaic (PV) showed an average current of 0.74 amperes (A), an average voltage of 18.7 volts (V), and an average power output of 14.4 watts. (W). Meanwhile, measurement results without a solar tracker showed an average current of 0.6 amperes (A), an average voltage of 17.9 volts and an average power output of 11.04 watts (W). So, the power produced with a solar tracker is more optimal than without a solar tracker.